Multimodality in a diachronic light: Tracking changes in text-image relations within the genre profile of the MIT Technology Review. (December 2017) - Stöckl, Hartmut
Abstract: The present study tracks historical changes in the genre profiles, image types, and text-image relations of the MIT Technology Review over 113 years. Within the framework of sociolinguistic mediatization research, observable changes are linked to factors or trends that influence media development generally, such as graphic salience, communicative directness or reversal of aesthetic preferences. Rather than produce ultimate results about genre and multimodal change in popular science writing, the contribution seeks to outline a method for analysis which combines genre and illustration profiles, image types, multimodal rhetorical clusters and conjunctive text-image relations. The application of the proposed method yields clear results: Genre profiles broaden and typical popular science genres emerge; multimodal rhetorical clusters diversify and visualization generally intensifies; the internal structure of individual clusters shifts. Based on an exemplary exploration of the method, the present contribution suggests ways of refining text linguistic and multimodal research of the historical type. Direct correlations between observed textual and multimodal change and changes in media logic prove hard to draw, but large-scale studies are likely to reliably plot directions of media development and to pinpoint relevant influencing factors.